Financial Literacy: A Phenomenological Study Of Female MSME Activities From A Digital Marketing Perspective - Nuraisyiah; Muhammad Azis; Muhammad Hasan (International Journal of Education, Vocational and Social Science, 2025)
This study analyzes financial literacy from a digital marketing perspective in 15 women-owned MSMEs in Makassar City, spanning the service, culinary, beauty and personal care, and fashion sectors. The study was a qualitative study using phenomenological methods. The results indicate that understanding financial literacy helps women MSMEs conduct effective, efficient, and sustainable digital marketing.